Low markers of muscle damage and inflammation following a 3-day trail run - Denissen, EC; de Waard, AH; Singh, NR; Peters, EM (South African Journal of Sports Medicine, 2012)
Objectives. To investigate the effect of a 3-day trail run on markers of muscle damage and inflammation in recreational runners. Main outcome measures. Pre-and post-stage and 24-hour and 72- hour post-race concentrations of serum creatine phosphokinase (CPK), high sensitivity C-reactive Protein (hsCRP), cortisol, cardiac Troponin T (cTnT), and osmolality (sOsm) as well as urinary myoglobin (uMb), changes in body mass, delayed onset muscle soreness (DOMS) and thigh circumference (TC) were measured. Continuous recordings of heart rate (HR) and intestinal temperature (Tintest ) were made throughout each stage. Results. Heart rate ranged between 77% and 83% age-predicted maximum (APmax) and Tintest between 36.1 and 40.2ºC during the three stages. Significant rises in mean serum CPK, hsCRP, sOsm and blood neutrophil count reached peak concentrations of 1488U/l, 8.91mg/l, 298mosm/l and 10.21 109/l (p<0.001), respectively. No evidence of elevations in uMb and cTnT were detected. The stage-induced increments in DOMS correlated positively with CPK, r=0.71; 95% CI [0.62, 0.78], TC decreased significantly post S1post and S2post (p<0.05) and a maximum mean body mass loss of 3.09% (±1.04%) occurred during S2. Conclusion. Three consecutive days of 95-km trail running resulted in low markers of muscle damage and inflammation, despite the maintenance of a heart rate above 77% APmax, Tintest rising above 39oC and mean body mass decrement of >2.0%.